Bibliometric analysis of international publication trends on social media and terrorism by using the Scopus database - Yumitro, Gonda; Febriani, Rizki; Roziqin, Ali; Indraningtyas, Anisa (Frontiers in Communication, 2023)
Social Media and Terrorism are often studied together and have become the focus of many authors in recent years. Therefore, this study aims to evaluate international publication trends on social media and terrorism, using the Scopus database through bibliometric analysis from 2009 to 2022. Data visualization and analysis were conducted using Microsoft Excel and VOSviewer. The results showed that the international publications trend reached a peak in 2018, with 103 publications emphasizing various topics, such as social media, terrorism, Twitter, terrorist attacks, and several issues related to terrorist activities and digital platforms. The United States was also the most common country of publication with the highest number of affiliated authors. In addition, the authors with the most published documents were Tsikrika T. and Vrochidis S., with the majority of reports prioritizing social sciences. These results are expected to contribute to the novelty of previous studies on social media and terrorism.